Effect of age on the intracortical accumulation kinetics of gentamicin in rats. - Beauchamp, D (1989)
We have evaluated the influence of age on the intracortical accumulation kinetics of gentamicin in conscious male rats by using a short-term infusion model. Animals were infused with gentamicin over a 6-h period and achieved individual steady-state levels in serum ranging from 0.5 to 12 micrograms/ml. Young rats were about 3 months old, and old rats were about 6 months old. The steady-state elevation of concentrations of gentamicin in serum was associated with a linear increase of the cortical concentrations in both groups. However, the accumulation of gentamicin was lower in the renal cortex of the old rats than in the renal cortex of the young rats. We conclude that the intrarenal uptake of gentamicin is modified during aging. Further studies must be undertaken to better understand the role of age on the mechanism of uptake and the toxicity of aminoglycosides.